Analisis Teknis Sistem Proteksi Kebakaran di Pasar Segiri Kota Samarinda: Analisis Teknis Sistem Proteksi Kebakaran di Pasar Segiri Kota Samarinda - claudia nur alyasari; Suwignyo; istiarto (Universitas Widya Gama Mahakam Samarinda, 2023)
Abstract Background: The market is one of the public facilities that often experiences fires because it has a high density of occupants and goods so that fires can have an impact on the area around the market. Objectives: The purpose of this study was to find out the technical fire protection system in Segiri Market, Samarinda City. Research Metodes: Uses a qualitative method with a descriptive approach. This research was conducted at Segiri Market. Informant selection technique with purposive sampling, amounting to 4 people and data collection techniques with interviews, observation, and documention. Results: There are no emergency response procedures, site completeness such as a water source in the form of the Karang Mumus River whivh is behind the market, there are 2 environmental road access points, namely the main route with a width of ± 10 m and the mosque route with a width of ± 5 m and there are bend with a width of ±2.5 m, there are no yard hydrants and gathering points. Then active and passive protection systems are not available and no means of exit are provided at the Segiri Market. Conclusion: Make fire emergency response procedures, pay attention to environmental road access, namely the width of the bend in the mosque lane with a minimum requirement of 4 m, 54 yard hydrants, provide assembly points with provisions of 0.3 m2/person, active and passive protection systems such as 306 dry chemical powder fire extinguishers, 250 sprinklers and building hydrants connected to the sprinkler. Then providing fire alarms with 60 manual call points, replacing building materials with gypsum materials and carrying out fire resistance tests as well as providing 4 access exit facilities with evacuation route signs Keywords: Fire, Market, Active and Passive Protection Systems